Sequence of the Gonium pectorale Mating Locus Reveals a Complex and Dynamic History of Changes in Volvocine Algal Mating Haplotypes. Issue 5 (1st May 2016) - Hamaji, Takashi; Mogi, Yuko; Ferris, Patrick J; Mori, Toshiyuki; Miyagishima, Shinya; Kabeya, Yukihiro; Nishimura, Yoshiki; Toyoda, Atsushi; Noguchi, Hideki; Fujiyama, Asao; Olson, Bradley J S C; Marriage, Tara N; et al.
Abstract: Sex-determining regions (SDRs) or mating-type ( MT ) loci in two sequenced volvocine algal species, Chlamydomonas reinhardtii and Volvox carteri, exhibit major differences in size, structure, gene content, and gametolog differentiation. Understanding the origin of these differences requires investigation of MT loci from related species. Here, we determined the sequences of the minus and plus MT haplotypes of the isogamous 16-celled volvocine alga, Gonium pectorale, which is more closely related to the multicellular V. carteri than to C. reinhardtii . Compared to C. reinhardtii MT, G. pectorale MT is moderately larger in size, and has a less complex structure, with only two major syntenic blocs of collinear gametologs. However, the gametolog content of G. pectorale MT has more overlap with that of V. carteri MT than with C. reinhardtii MT, while the allelic divergence between gametologs in G. pectorale is even lower than that in C. reinhardtii . Three key sex-related genes are conserved in G. pectorale MT : GpMID and GpMTD1 in MT –, and GpFUS1 in MT +. GpFUS1 protein exhibited specific localization at the plus -gametic mating structure, indicating a conserved function in fertilization. Our results suggest that the G. pectorale–V. carteri common ancestral MT experienced at least one major reformation after the split from C. reinhardtii, and that the V. carteri ancestral MT underwent a subsequent expansion and loss of recombination after the divergence from G. pectorale . These data begin to polarize important changes that occurred in volvocine MT loci, and highlight the potential for discontinuous and dynamic evolution in SDRs.